Minecraft as a Hybrid Boundary Object: Exploring Nature in Squares - Anne-Marie Cederqvist; Maria Impedovo (MDPI AG, 2023)
In this exploratory case study, we investigated children's ways of experiencing virtual worlds, such as Minecraft, and how this may affect their understanding of nature, scientific phenomena, and sustainable development; that is to say, Minecraft was explored as a boundary object in children's making activities with Minecraft. The research questions that guided the study are: In what ways may Minecraft act as a boundary object between children's formal and informal learning about science and sustainable development? In what ways may Minecraft act as a boundary object when children build relationships with nature? Semi-structured interviews were conducted with six children. A thematic analysis approach was used to analyze the interviews. This study shows that in the Minecraft context, the children gained a breadth of everyday experiences related to scientific phenomena and sustainability. Further, the findings indicate that children merged their experiences in the virtual world with experiences in the physical world. In this sense, Minecraft involves science and sustainability content that crosses the boundary between the virtual world and reality. Thus, we suggest that Minecraft bridged children's physical and virtual relationships with nature; that is to say, Minecraft became a boundary object that allowed children to experience nature and encounter knowledge that they would not otherwise have been able to experience.